Proceedings of the IEEE 2002 International Interconnect Technology Conference (Cat. No.02EX519)
DOI: 10.1109/iitc.2002.1014913
|View full text |Cite
|
Sign up to set email alerts
|

Electromigration failure mechanism studies on copper interconnects

Abstract: Electromigration (EM) studies revealed a strong correlation between observed failure scenario and local microstructural properties at the via-to-line-transition, in particular that of the liner. "Early" failure modes were found to have not only smaller failure times but also a lower current density exponent. The influence of specific processes on the occurrence ofcertain failure modes will he discussed. IntroductionThe EM resistivity of bulk copper is known to be larger compared to AI(Cu) [I]. However, failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 4 publications
2
34
0
Order By: Relevance
“…(17) may be very limited if one uses the Damascene configuration where the electric contacts are established at the lower surfaces of the anode and cathode edges of the interconnects lines having top surface acting as dominant diffusion path because of no capping (trenchvoiding), as it was the case of Hu et al (1997) and Fischer et al (2002). Then, Eq.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…(17) may be very limited if one uses the Damascene configuration where the electric contacts are established at the lower surfaces of the anode and cathode edges of the interconnects lines having top surface acting as dominant diffusion path because of no capping (trenchvoiding), as it was the case of Hu et al (1997) and Fischer et al (2002). Then, Eq.…”
Section: Discussionmentioning
confidence: 98%
“…This opposes our presumption that the electrical contact to the specimen is established at the cathode edge by the DMCE without soldering. However, this concept of CCFT by voiding still may be applied to Cu-Damascene interconnect line under very special conditions, namely; the via regions are the natural extension of the test specimen similar to Cu-via and the surface is capped with metal coating (CoWP, CoSnP, or Pd) to inhibit SN x coated top interface from acting as a fast drift-diffusion path (Hu et al, 2002(Hu et al, , 2004Fischer et al, 2002). According to experimental findings, (Hu et al, 2002), mostly the via-bottom void is observed in the capped samples, which is a strong indication that the sidewall and via-bottom interfaces may play dominate diffusion paths rather than the top surface or interfacial layer.…”
Section: Constant Current Experiments CCmentioning
confidence: 98%
See 1 more Smart Citation
“…All structures were investigated under normally chosen test conditions [1,2,8]. The applied current density was varied between 0.3 MA/ cm 2 and 25 MA/cm 2 .…”
Section: Simulation Conditionsmentioning
confidence: 99%
“…A calculation routine based on FORTRAN is used for the determination of the local mass flux divergences and the dynamic void formation in the model. First the suitability of the simulation and calculations will be shown by the determination of the void formation for a copper interconnect structure taken from the literature [2]. For comparison of the different influences default models were created.…”
Section: Introductionmentioning
confidence: 99%